Progressive Web App (PWA) Sebagai Solusi Aksesibilitas Sistem Informasi Akademik - Olivia, Melvina (CV. Generasi Insan Rafflesia, 2024)
The academic information system is a system built to facilitate academic administration activities in educational institutions and is carried out online. Academic data processing still uses sheets of paper and archives (manual), causing existing data to be easily lost or damaged and searching for data takes a long time. The purpose of this research is to design a web-based academic information system to support operational activities and make it easier for schools to deliver information by applying Progressive Web Apps (PWA) to make easy access for student teachers when entering applications with mobile web displays on smartphone devices. The testing method used is the black-box testing method, namely the system is executed through trials and checks the functionality of the web application. The results of testing this application students, teachers, principals login to enter the main display. The main menu has student data, teacher data, assessments, assessments, lesson schedules and profile pages. The conclusion of testing the information system is as desired by the school in providing convenience in conveying information and the application can run well and no bugs are found.